Kemampuan Pemecahan Masalah Siswa pada Materi Optika Geometri - Zidni Ansori; Wartono Wartono; Sutopo Sutopo (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The purpose of this study is to determine to what extent students' problem solving skill on geometric optical topic. The method used was survey on 34 students of XI graders at SMA Negeri 9 Malang who have obtained optical geometry lesson. The average score of problem solving skill of students was 61,12, with the highest score was 184 and the lowest score was 34. The result of the research shows that students problem solving ability in the novice category is bigger than expert category,thus it needs to implement learning which improves students problem solving ability.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana kemampaun pemecahan masalah siswa pada materi optika geometri. Metode yang digunakan dengan survei pada 34 siswa kelas XI SMA Negeri 9 Malang yang telah memperoleh pelajaran optika geometri. Nilai rata-rata kemampuan pemecahan masalah siswa sebesar 61,12 dengan nilai tertinggi adalah 184 dan nilai terendah 34. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah siswa dalam kategori novice lebih besar daripada kategori expert, sehingga perlu diterapan pembelajaran untuk meningkatkan kemampuan pemecahan masalah siswa.